Therapeutic potential of taxanes in the treatment of metastatic pancreatic cancer - Lemstrova, Radmila; Melichar, Bohuslav; Mohelnikova-Duchonova, Beatrice (Cancer chemotherapy and pharmacology, 2016)
Most patients with pancreatic ductal adenocarcinoma (PDAC) present with unresectable or metastatic disease with very poor prognosis. Chemotherapy is the primary treatment modality for patients with locally advanced and metastatic PDAC, but the efficacy of currently available regimens is limited. Taxanes are widely used in many primary cancers including breast, ovarian and lung cancers. The activity of combined regimen of taxanes plus nucleoside analogue or platinum derivate in terms of response rate ranges between 20 and 57 % in PDAC and may prolong overall survival. Since 2013 nab-paclitaxel (paclitaxel-albumin-bound particles) became a new treatment option for patients with metastatic pancreatic cancer based on the results of MPACT trial. Moreover, encouraging activity in PDAC of the combination regimen of paclitaxel and carboplatin that is being widely used in other solid tumors has been reported recently. Biomarkers, including biomarkers predictive of taxane resistance, could allow individualized tailored therapy. BRCA mutation status could serve as predictor of better chemotherapy treatment outcome in PDAC. The present review summarizes the principal clinical trials evaluating the efficacy of taxanes both as monotherapy and in combination in view of the potential use in the treatment of PDAC.
Keywords: Taxane; Neoplasm Metastasis; klinické zkoušky jako téma; nádory slinivky břišní; Paclitaxel; metastázy nádorů; Antineoplastic Combined Chemotherapy Protocols; Docetaxel; Taxoids; Drug resistance; Carcinoma, Pancreatic Ductal; lidé; duktální karcinom slinivky břišní; Clinical Trials as Topic; taxoidy; protokoly protinádorové kombinované chemoterapie; Nab-paclitaxel; chemorezistence; Humans; Pancreatic Neoplasms; Pancreatic cancer; Drug Resistance, Neoplasm